The Neglected Dimension - Rahadiningtyas, Anissa (National Gallery Singapore, 2023)
The Neglected Dimension offers an insight into a moment in Southeast Asian modern art when a group of artists from the city of Bandung, Indonesia reimagined Arabic calligraphic writing. At the heart of this effort was an art school at Institut Teknologi Bandung (ITB), which stood at the forefront of experimentations with forms of Islamic spirituality and abstraction. Four artists are featured in this exhibition: Ahmad Sadali (1924-1987), A.D. Pirous (b. 1932), Haryadi Suadi (1938-2016) and Arahmaiani (b. 1962). They represent three generations of artistic training at ITB, as well as distinct approaches to calligraphic abstraction that reflect changing values, identities and conventions in Indonesia from the 1970s to the present. Together, their works highlight how they interacted with global conventions in modern art, evolving ideas around Islamic spirituality, feminist activism and the experience of being Muslim in Indonesia.